Ablative fractional carbon dioxide laser combined with intense pulsed light for the treatment of photoaging skin in Chinese population: A split-face study. Issue 3 (January 2018) - Mei, Xue-Ling; Wang, Li
Abstract : Abstract: Intense pulsed light (IPL) is effective for the treatment of lentigines, telangiectasia, and generalized erythema, but is less effective in the removal of skin wrinkles. Fractional laser is effective on skin wrinkles and textural irregularities, but can induce postinflammatory hyperpigmentation (PIH), especially in Asians. This study evaluated the safety and efficacy of ablative fractional laser (AFL) in combination with IPL in the treatment of photoaging skin in Asians. This study included 28 Chinese women with Fitzpatrick skin type III and IV. The side of the face to be treated with IPL alone (3 times) or AFL in combination with IPL (2 IPL treatments and 1 AFL treatment) was randomly selected. Skin conditions including hydration, transepidermal water loss, elasticity, spots, ultraviolet spots, brown spots, wrinkle, texture, pore size and red areas, as well as adverse effects were evaluated before the treatment and at 30 days after the treatment. Compared with IPL treatment alone, AFL in combination with IPL significantly increased elasticity, decreased pore size, reduced skin wrinkles, and improved skin texture ( P = .004, P = .039, P = .015, and P = .035, respectively). Both treatment protocols produced similar effects in relation to the improvement of photoaging-induced pigmentation. The combined therapy did not impair epidermal barrier function. No postoperative infection, hypopigmentation, or scarring occurred after IPL and AFL treatments. PIH occurred at 1 month after AFL treatment and disappeared at 30 days after completion of the combined therapy. AFL in combination with IPL is safe and effective for photoaging skin in Asians.